Gambaran Resiliensi Remaja Akhir Laki-Laki Yang Pernah Mengalami Perundungan Di Sekolah - Kasela , Felicia; Chrisnatalia, Desy (Atma Jaya Catholic University of Indonesia, 2025)
Bullying is a common phenomenon among adolescents, particularly in school settings. It involves acts of violence against individuals perceived as weaker within the school environment. Victims of school bullying may experience lasting negative effects that persist into late adolescence. Resilience, the ability to navigate and recover from difficult experiences, plays a crucial role in helping individuals cope with adversity. Research has identified differences in resilience between males and females, but there is limited exploration of resilience specifically in late adolescent males who have experienced bullying in schools. This study aims to examine resilience among late adolescent males who have faced bullying in schools. Using a qualitative approach with a thematic reflexive analysis, data was collected through semi-structured interviews with three late adolescent male participants, and then analyzed thematically. The findings indicate that all three participants demonstrate resilience in their current lives, reflected in key aspects such as emotional regulation (managing emotions effectively), impulse control (restraining harmful impulses), optimism (maintaining positive expectations for the future), causal analysis (recognizing bullying as a result of power imbalance), empathy (understanding the emotions of others), self-efficacy (confidence in their own abilities), and reaching out (taking initiative to achieve results). Additionally, social support played a significant role in fostering resilience among the participants.